Unit sliding mode control in infinite dimensional systems - Orlov, Yuri; Utkin, Vadim I. (Zielona Góra: Uniwersytet Zielonogórski)
In contrast to the conventional component-wise design of sliding mode control, a new approach is developed for infinite-dimensional systems. The conventional approach is not applicable since, generally speaking, the infinite-dimensional control may not be represented in the component form as well as a sliding manifold.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka